Cardiolipin Binds to CD1d and Stimulates CD1d-Restricted γδ T Cells in the Normal Murine Repertoire - Mélanie Dieudé; Harald Striegl; Aaron J. Tyznik; Jing Wang; Samuel M. Behar; Ciriaco A. Piccirillo; Jerrold S. Levine; Dirk M. Zajonc; Joyce Rauch (2011)
Cardiolipin (CL), a major phospholipid in bacterial cell walls, is sequestered from the immune system in mammalian mitochondria and is, therefore, a potential danger signal. Based on growing evidence that phospholipids constitute natural ligands for CD1 and that CD1d-restricted T cells recognize phospholipids, we hypothesized that CD1d binds and presents CL and that T cells in the normal immune repertoire respond to CL in a CD1d-restricted manner. We determined the murine CD1d-CL crystal structure at 2.3 Å resolution and established through additional lipid loading experiments that CL, a tetra-acylated phospholipid, binds to murine CD1d with two alkyl chains buried inside the CD1d binding groove and the remaining two exposed into the solvent. We furthermore demonstrate the functional stimulatory activity of CL, showing that splenic and hepatic γδ T cells from healthy mice proliferate in vitro in response to mammalian or bacterial CL in a dose-dependent and CD1d-restricted manner, rapidly secreting the cytokines IFN-γ and RANTES. Finally, we show that hepatic γδ T cells are activated in vivo by CD1d-bearing dendritic cells that have been pulsed with CL, but not phosphatidylcholine. Together, these findings demonstrate that CD1d is able to bind and present CL to a subset of CL-responsive γδ T cells that exist in the spleen and liver of healthy mice and suggest that these cells could play a role in host responses to bacterial lipids and, potentially, self-CL. We propose that CL-responsive γδ T cells play a role in immune surveillance during infection and tissue injury.